Diagnosis and treatment of resistant periapical pathoses at the maxillary anterior region: a case report - Pinto, Antonione Santos Bezerra; Galvao, Neiandro dos Santos; Dias, Luis Paulo da Silva; Mendes, Jean de Pinho; Lopes, Sérgio Lúcio Pereira de Castro; Costa, André Luiz Ferreira (Journal of Oral Diagnosis, 2016)
The objective of this study was to report a clinical case of periapical pathosis at the maxillary anterior region which was resistant to conventional endodontic treatment and discuss the contribution of the magnetic resonance imaging (MRI) to the diagnostic process. Female patient aged 43 years old was referred to specialised dental care following unsuccessful endodontic treatment of tooth #11, which had been carried out after presumptive diagnosis of granuloma or root cyst. For a better evaluation, periapical radiography, cone beam computed tomography and MRI exam were all indicated. By means of these exams, one could observe the presence of another lesion at the region of tooth #13, which was suggestive of residual cyst. On MRI scan, the T2WI of the lesions showed hypersignal areas compatible to inflammatory process. Surgery excision of the lesions and apicoectomy of tooth #11 were the treatments chosen, including further referral for histopathological exam. Final diagnosis of both lesions was non-specific inflammatory process or dental granuloma. Clinical-radiographic control showed area of new bone formation, thus evidencing bone repair process. One can conclude that the diagnosis and treatment of periapical pathoses may be challenging and that MRI contributed by providing important information on the nature and content of these lesions.